Literature Review : Pengaruh Persepsi E-Commerce, Modal Usaha, dan Penggunaan Sistem Informasi Akuntansi Terhadap Keputusan Berwirausaha - Mutiara Oktaviani Putri; Ersha Wiriani Safitri; Nadia Fitri Ramadani; Agustiawan Agustiawan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
An important component of any research or scientific article is relevant research. The thing that makes individuals less interested in entrepreneurship is because they are not yet aware of their abilities and intentions in carrying out business in realizing their dreams of becoming successful entrepreneurs. The purpose of this research is to examine how perceptions of e-commerce, business capital and the application of accounting information systems influence decision making in entrepreneurship. The findings of this literature study show that perceptions of e-commerce and the use of accounting information systems influence entrepreneurial decisions, business capital has no influence and is not significant on entrepreneurial decisions.